Analyzing Hedgehog pathway-related genes: insights into breast cancer tumor microenvironment and prognostic implications - Wang, Ziyun; Wang, Hua (Frontiers in Immunology, 2025)
Study objectivesGiven the significant global burden of breast cancer, this study aims to systematically explore the role of Hedgehog (Hh) pathway-related genes in breast cancer prognosis and immunological characteristics. Additionally, we will construct a risk scoring system based on this pathway, with the objective of providing new references for prognostic assessment and immunotherapy strategies.MethodsKey Hh-related genes were identified, and Hedgehog scores were calculated for each sample using the ssGSEA algorithm. These scores were integrated with clinical data. Patients were classified into high-risk and low-risk groups, which were analyzed regarding immune factors, metabolic characteristics, gene mutations, and clinical outcomes.ResultsSignificant associations were found between the high-risk group and drug sensitivity, immune scores, and overall survival. The findings suggest that immunotherapy may serve as a valuable prognostic tool in breast cancer treatment.ConclusionsThis study presents a reliable prognostic system based on the Hh pathway score for breast cancer prognosis and drug responsiveness. The results underscore the potential of immunotherapy in improving prognosis and emphasize the need for further clinical validation.